FGFR2 genomic aberrations: Achilles heel in the management of advanced cholangiocarcinoma. (August 2019) - Mahipal, Amit; Tella, Sri Harsha; Kommalapati, Anuhya; Anaya, Daniel; Kim, Richard
Abstract: Cholangiocarcinoma is the most common aggressive biliary tract malignancy with dismal prognosis. Though surgical resection of the primary tumors yields better prognosis, majority of patients present at advanced, inoperable stages rendering systemic therapy as the only option. A significant progress has been made in understanding the cholangiocarcinoma tumorigenesis and molecular markers over the last decade, which opens doors to precision medicine in this dismal cancer. Intrahepatic cholangiocarcinomas are most likely to harbor mutations in isocitrate dehydrogenase genes ( IDH1, IDH2 ), fibroblast growth factor receptors ( FGFR1, FGFR2, FGFR3 ), Eph receptor 2 ( EPHA2 ), and BAP1 (gene involved in chromatin remodeling) genes, whereas ARID1B, ELF3, PBRM1, cAMP dependent protein kinase ( PRKACA, and PRKACB ) genetic mutations were implicated more commonly in distal and perihilar subtypes. Genomic studies have shown that FGFR2 aberrations are implicated in approximately 15% of intrahepatic cholangiocarcinomas, which make FGFR2 aberrations (Achilles heel) as potential novel targets in the management of cholangiocarcinoma. The current review comprehensively focuses on the role of FGFR2 inhibition either alone or in combination with other targeted therapy that act on down-stream and alternate kinase pathways in cholangiocarcinoma.